The Influence of Free Cash Flow and Debt To Equity Ratio to Earnings Management - Alex Nurdiana (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The separation functions between management and stockholders can create the opportunities to do earnings management. This study aimed to analyze the influence of free cash flow and debt to equity ratio to earnings management. This type of research is a causal research, which aims to test the hypothesis about the effect of an independent variable on the dependent variable. The research method is quantitative research. Samples are 83 companies listed in the Indonesia Stock Exchange (BEI) 2011-2013. The sampling method is purposive random sampling. The results of this study stated that free cash flow has negative effect on earnings management. Debt to equity ratio has no effect to earnings management. Leverage has positive effect on earnings management. Age of Companies has no effect on earnings management. Gross margin has no effect on earnings management. The coefficient of determination obtained from the results of this study indicate that the independent variables can explain the dependent variable of 10.2%, while the remaining 89.8% is influenced by other variables not examined in this study.